Age variation of motor nerve conduction study in healthy adults: A physiological reference - Sunil Kumar Jena; Manoranjan Acharya (Wolters Kluwer Medknow Publications, 2023)
Background: Nerve conduction study (NCS) is the simple noninvasive technique to assess the functional status of peripheral nerves. Physiological variables such as age, sex, anthropometric indices influence the functional status of peripheral nerves. Hence, this study was designed to assess the effect of age on motor NCS. Materials and Methods: A cross-sectional study was done among healthy adults of different age group to observe the effect of age on nerve conduction. Ninety-eight healthy study participants were selected for this study after getting due approval from ethics committee of the institution. Motor NCS was performed with the standard procedure by trained technician under supervision of neurologists. Median, ulnar, posterior tibial, and common peroneal nerve (CPN) were studied for compound motor action potential. All study participants were classified into three groups according to their age, i.e., Group A (20-35 years), Group B (36-50 years), and Group C (>50 years). Statistical test one way ANOVA was used to analyze the data. Results: Distal latency of older age group participants was prolonged than younger age group. Amplitude in older age group participants was less than younger age group only in median and CPN. Conduction velocity in older age group is less in comparison to younger age group. Conclusion: This study opined age has substantial role in NCS of healthy subjects. Hence, age reference data of motor NCS are helpful for the evaluation of functional status of motor nerves.